Variable humic product effects on maize structural biochemistry across annual weather patterns and soil types in two Iowa (U.S.A.) production fields - Olk, D. C.; Dinnes, D. L.; Hatfield, R. D.; Scoresby, J. R.; Darlington, J. W. (Frontiers in Plant Science, 2023)
Agronomic benefits of humic product application to crops are receiving increasing attention, though underlying biochemical changes remain unexplored, especially in field settings. In this study, maize (Zea mays L.) concentrations of 11 phenol and five carbohydrate monomers were determined in whole plant stover (four growing seasons) and roots (two growing seasons) at physiological maturity for two rainfed fields in Iowa (USA) having humic product applications. Stover and root tissues tended toward greater phenol concentrations in a drier upland transect but greater carbohydrate concentrations in a wetter lowland transect. Two humic treatments further accentuated these trends in upland roots. Their phenol content increased significantly with humic application in the droughtier season of root sampling (2013). Phenol increases above the unamended control averaged 20% for each monomer. Total phenols increased above the control by 12% and 19% for the two humic treatments. Five carbohydrate monomers in the upland roots did not respond to humic application. In the second year of root sampling (2014), which had abundant rainfall, upland root phenols did not respond substantively to humic application, but root carbohydrates increased on average by 11 or 20% for the two humic treatments compared to the control, reaching significance (P< 0.10) in 7 of 10 cases. Upland stover phenol concentrations responded differently to humic product application in each of four years, ranging from numeric increases in the droughtiest year (2012) to significant decreases with abundant rainfall (2014). In the lowland transect, root phenols and carbohydrates and stover phenols responded inconsistently to humic application in four years. Stover carbohydrates did not respond consistently to humic application in either transect. The phenols that were more responsive to humic application or to droughtier conditions included p-coumaric acid and syringaldehyde, which are heavily involved in late-season maize lignification. In summary, humic product application further promoted root lignification, a natural response to drought. Yet under non-drought conditions it promoted root carbohydrate production. Carbohydrate production might be the intrinsic plant response to humic product application in stress-free conditions. These results indicate complex interactions in field conditions between plant biochemistry, environmental signals, and the humic product.